2014
DOI: 10.1039/c3cc48398c
|View full text |Cite
|
Sign up to set email alerts
|

Water-stable metal–organic frameworks with intrinsic peroxidase-like catalytic activity as a colorimetric biosensing platform

Abstract: Two iron(III)-based metal-organic frameworks (MOFs) are found to behave as efficient peroxidase mimics and catalyze the oxidation of different peroxidase substrates by H2O2 accompanied with significant color change in the solution. With these findings, a simple and sensitive colorimetric assay to detect H2O2 and ascorbic acid has been established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
145
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 343 publications
(153 citation statements)
references
References 37 publications
8
145
0
Order By: Relevance
“…Therefore, MOFs have been recognized as one of the important functional nanoporous materials in small-molecule sensing, separation, and catalysis [16][17][18]. Thus, various analytical applications of MOFs are growing rapidly in the past few years [19][20][21][22][23]. For example, MOFs have been explored as promising luminescent materials for sensing various targets [19,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, MOFs have been recognized as one of the important functional nanoporous materials in small-molecule sensing, separation, and catalysis [16][17][18]. Thus, various analytical applications of MOFs are growing rapidly in the past few years [19][20][21][22][23]. For example, MOFs have been explored as promising luminescent materials for sensing various targets [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…For example, MOFs have been explored as promising luminescent materials for sensing various targets [19,20]. Recently, MOFs have been reported to show peroxidase-like catalytic activity [21][22][23] for Published in the topical collection Highlights of Analytical Chemical Luminescence with guest editors Aldo Roda, Hua Cui, and Chao Lu.…”
Section: Introductionmentioning
confidence: 99%
“…It is recently reported that some MOFs show peroxidase-like catalytic activities, catalyzing the oxidation of o-phenylenediamine (OPD) with obvious color change of solution in the presence of hydrogen peroxide (H 2 O 2 ). 56,57 As a proof of concept, the visual detection of H 2 O 2 using HKUST-1 decorated nanober membrane as catalyst is demonstrated here. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In particular,b ecause of their tunable structures and chemical compositions, and superior properties, nanostructured material-based enzyme mimetics, including Fe 3 O 4 nanoparticles, [2][3][4] ZnFe 2 O 4 nanoparticles, [5] CeO 2 nanoparticles, [6] Au@Pt nanoparticles, [7] Fe-Co alloy nanoparticles, [8] Co 3 O 4 nanoparticles, [1] V 2 O 5 nanowires, [9] carbon nanodots, [10] carbon nanotubes, [11,12] graphene oxide, [13] and metal-organic frameworks (MOFs), [14][15][16][17] have been investigated extensively.A mongt hese, mostp apers focusedo np owdered nanostructured materials, but nanoscale powders are difficult to recover forr euse. We adopt hydroxyapatite nanowires (HAPNWs) and MIL-100(Fe) (MIL = MaterialI nstitute de Lavoisier) [24] as raw materials and the template-directed layer-by-layer (LBL) deposition methodt op reparet he HAP@MIL-100(Fe) NFs for the following reasons: 1) ultralong HAPNWs have been used successfully as buildingb locks for the preparation of an ew kind of highlyf lexible, fire-resistant inorganic paper; [22,23] 2) it has been demonstrated that MIL-100(Fe)n anocrystals have peroxidase-like activity, [16] and highdensity active metal centers inside their 3D frameworks contribute significantly to the enhancemento ft he catalytic activity; [25] 3) the template-directed synthesis is as imple, straightforward, and well-developed route for in situ nucleation and growth of nanocrystals; [26] 4) the Coulombic and chelationi nteractions between inherentC a 2 + ions on the surfaceo ft he HAPNWs and the organic linkers (COO À )o fM IL-100(Fe) will induce the initial nucleation and subsequent growth of the nanocrystals, avoiding complicated surface modification; [27,28] 5) the layer-by-layer method allows uniform depositiona nd precise thickness control, and hence, tunable catalytic activity of the enzyme-mimetic HAP@MIL-100(Fe) NFs; [27,29] 6) the intrinsically high specific surfacea rea (S BET )a nd porouss tructure of MOFs facilitate the diffusion of the molecules and ions into catalytic active centers, which benefits the catalytic reaction; [2...…”
Section: Introductionmentioning
confidence: 99%